A Comprehensive Analysis of the Behavior of Pelvic Incidence After Different Posterior Spinal Procedures in Elderly Patients With Spinal Deformity. Issue 2 (March 2023) - Zhu, Weiguo; Wang, Yu; Kong, Chao; Sun, Xiangyao; Pan, Fumin; Wang, Wei; Lu, Shibao
Study Design: A retrospective case-control study. Objective: To evaluate the behavior of pelvic incidence (PI) after different posterior spinal procedures in elderly patients with adult spinal deformity (ASD), to determine the potential associated factors with the variability in PI after spinal surgery and to comprehensively analyze its mechanisms. Methods: Elderly patients underwent long fusion to sacrum with and without pelvic fixation were assigned to Group L+P and Group L-P, respectively. In Group L-P, those with severe sagittal deformity were selected as Group A. 20 elderly patients with severe sagittal deformity underwent short lumbar fusion were included as Group B. The following radiographic parameters were evaluated: thoracic kyphosis (TK), thoracolumbar kyphosis (TLK), lumbar lordosis (LL), PI-LL, sagittal vertical axis (SVA), T1 pelvic angle (TPA), and pelvic parameters. PI changing more than 5° (△PI > 5°) was considered as substantially changed. Results: For the whole cohort and in Group L+P, PI were not substantially changed (△PI ≤ 5°) after surgery. Besides the severer sagittal malalignment in patients with △PI > 5° in Group L-P, relatively larger mean age, greater proportion of female and lower preoperative PI were found than those in patients with △PI ≤ 5°. 70.8% of patients had substantial increase of PI in Group A, while only 10% of patients had in Group B ( P < 0.001). Conclusion: PI behaves differently under different conditions in elderly ASD patients. Besides severe sagittal deformity, aging, female and low preoperative PI are also the potential risk factors of PI increasing after long fusion to sacrum.